Pendampingan Pembuatan Media Pembelajaran Klopedimatika Berbasis Kearifan Lokal Madura - Septi Dariyatul Aini; Sri Indriati Hasanah; Fetty Nuritasari; Madinatul Munawwaroh; Sri Wahyuni (Institut Teknologi dan Bisnis Semarang, 2023)
The use of clopedimatics learning media based on local Madurese wisdom is very beneficial for students, apart from preserving Madurese culture, it is also able to increase students' interest in mathematics. If students are interested and like mathematics, then mathematical concepts will be easier to understand. However, based on observations and interviews with the Principal of SDN Barkot I Pamekasan and students, information was obtained that: (1) the majority of teachers have not created certain learning media to accompany existing handbooks, (2) there is a lack of enthusiasm among students to learn mathematics, (3) ) students' lack of knowledge of Madurese local wisdom. The aim of this service is to provide solutions to partners by assisting in the creation of clodimatics learning media based on local Madurese wisdom. In general, the targeted outputs are: (1) there is an increase in partners' knowledge about clopedimatics learning media based on Madurese local wisdom (2) Implementation of Madurese local wisdom-based clopedimatics learning media in learning (3) articles in national journals with ISSN and electronic mass media, (4) Activity videos on YouTube